Philippine Army Finance Center Producers Integrated Cooperative A case study on democratization and development. - Arcales, Sherry Mae A. (Tacloban City Sherry Mae A. Arcales, 2009)
For the past decades, cooperatives have been the primary engines of development and democratization, not just in the Philippines, but also in other parts of the globe. Through their various services and programs, these organizations bring about economic and political empowerment to the people in the community in which they are located.
This study focused on the various roles of the Philippine Army Finance Center Producers Integrated Cooperative in fostering democratization and development in the Philippines, particularly in Catbalogan, Samar. This research made use of a framework from trusted and reputable sources in order to examine and evaluate the various roles of the Philippine Army Finance Center Producers Integrated Cooperative in promoting democratization and development in Catbalogan, where the research was conducted.
This research study made use of six variables for its conceptual framework. These variables are a.) capital formation b.) member economic participation c.) democratic member control; d.) formation of political alliances; e.) popular participation and f.) saving by borrowing.
Through the series of interviews conducted as well as the important pieces of information gathered, it has been concluded that one of the major factors that entire a particular individual to join the cooperative is the abundant incentives which they could receive from the cooperative.
Undergraduate thesis (B.A.S.S. Political Science)--University of the Philippines, Tacloban
Keywords: Social Science